Building Envelope, HVAC Systems and RESs for the Energy Retrofit of a Conference Hall on Naples Promenade. (August 2015) - Ascione, Fabrizio; Bianco, Nicola; De Stasio, Claudio; Mauro, Gerardo Maria; Vanoli, Giuseppe Peter
Abstract: In central position on the suggestive promenade of Naples, the Conference Hall of the University of Naples Federico II is here studied, with the aim to suggest an energy retrofit strategy, effective and compatible with the high natural and historical values of the site. In detail, the impact of possible energy efficiency measures is investigated, by analyzing the feasibility of interventions concerning all levers of building energy performance (and thus thermal envelope, HVAC system, RESs). Because of the high quality of the building and of the site, all energy efficiency measures have been selected in order to be respectful of the unique scenario offered by this city area. Building Performance Simulations, performed by accurately modeling the building and the active energy systems, show that the kind of architecture and the destination of use (i.e., high occupancy and endogenous sensible and latent gains) favor an energy retrofit mainly based on the deep refurbishment of the HVAC system and on the installation of a photovoltaic plant.